Review of Carol Vernallis. 2013. Unruly Media: YouTube, Music Video, and the New Digital Cinema. New York: Oxford University Press. - Harper, Paula (Current Musicology, 2014)
“I love the media swirl,” begins Carol Vernallis’s (2013) Unruly Media. In this exploratory, whirlwind, and sometimes frustrating volume, Vernallis acts as an exuberant tour guide through the bleeding edges of twentieth– and twenty–first–century media content. Vernallis cares deeply about the material under scrutiny in her book—pop culture artifacts from the “Sneezing Baby Panda” video to Baz Luhrmann’s 2001 Moulin Rouge!—and the thesis of Unruly Media is, in part, that these objects are worthy of serious scholarly attention. Outing herself so blatantly as a fan of her material is a bold scholarly move, and, despite weaknesses in Unruly Media’s argumentation and execution, Vernallis’s call for further, rigorous, interdisciplinary attention to music video and other contemporary audiovisual phenomena is one that deserves to be heeded by scholars across a wide spectrum of disciplinary backgrounds.